An enhanced distortional-hardening-based constitutive model for hexagonal close-packed metals: Application to AZ31B magnesium alloy sheets at elevated temperatures. (March 2020) - Lee, Jinwoo; Bong, Hyuk Jong; Kim, Se-Jong; Lee, Myoug-Gyu; Kim, Daeyong
Abstract: In this study, a new material model for hexagonal close-packed (HCP) metals for predicting their flow responses under monotonic/cyclic loadings at various temperatures is proposed. The temperature-dependent constitutive model is re-formulated using a continuum-based distortional hardening law, which affects the shape of the yield surface depending on the loading direction, and also uses the concept of the dominant deformation modes in magnesium alloys: twin, untwin, and slip-dominate modes, considering the role of the twins in plastic deformation. In terms of the material asymmetry in yield strength, the Cazacu–Barlat–Plunkett (CPB) '06 yield criterion is extended to include thermal effects. A numerical formulation of the material model has also been developed to allow its implementation into finite element analysis software via a user-defined material subroutine (UMAT). The predicted results of stress–strain response for monotonic and cyclic loadings are excellent agreement with the experimental data. Moreover, the simulated results show the strength differential (SD) effect and unusual flow responses of AZ31B magnesium alloy sheets at room temperature, as well as the variation in the SD effect and anisotropic hardening behavior at elevated temperatures. Highlights: Enhanced distortional hardening law for HCP metals, particularly for targeting Mg alloys at warm temperatures, is proposed. The stress integration algorithm based on predictor-corrector scheme are formulated for the proposed constitutive model. Experimental results under strain path changes at various temperatures are accurately predicted using the proposed law. The Bauschinger effect under cyclic loadings is quantified, and the proposed constitutive model lead better prediction.